Identifikasi Gaya Belajar VAK Siswa Kelas VII SMP Negeri 17 Kota Jambi Pada Pembelajaran Matematika - Zahrotul Munawaroh; Silfia Delfina; Silvy Niara Sasky; Winati Diyah Wahyu Fatikasari; Novferma; Wardi Syafmen (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to identify the VAK (Visual, Auditory, Kinesthetic) learning method in seventh-grade students at SMP Negeri 17 Jambi City in the context of mathematics learning. The method used is descriptive qualitative. A total of 61 students from grades VII D2 and VII D3 became the subjects in this study. The instrument used was a VAK learning style questionnaire that had been translated into Indonesian and compiled by N, (2020), which was based on the Chislett & Chapman (2005) measurement tool. This questionnaire includes 30 multiple-choice questions that have been proven valid and reliable (Cronbach Alpha: Visual = 0.80; Auditory = 0.76; Kinesthetic = 0.78), supplemented by semi-structured interviews with teachers and documentation. Data analysis was carried out in three stages: data reduction, data presentation, and conclusion drawing. The results showed that the visual learning style was the most dominant, with 31 students (50.8%), followed by the kinesthetic learning style with 21 students (34.4%), and the auditory learning style with 9 students (14.8%). This pattern was consistent across both classes studied. These findings emphasize the need for mathematics teachers to make greater use of visual media and kinesthetic activities, while still meeting the needs of students with auditory learning styles through discussion and oral explanations.